Age‐related changes in aortic 3D blood flow velocities and wall shear stress: Implications for the identification of altered hemodynamics in patients with aortic valve disease. Issue 5 (19th October 2015) - van Ooij, Pim; Garcia, Julio; Potters, Wouter V.; Malaisrie, S. Chris; Collins, Jeremy D.; Carr, James C.; Markl, Michael; Barker, Alex J.
Abstract : Purpose: To investigate age‐related changes in peak systolic aortic 3D velocity and wall shear stress (WSS) in healthy controls and to investigate the importance of age‐matching for 3D mapping of abnormal aortic hemodynamics in bicuspid aortic valve disease (BAV). Materials and Methods: 4D flow MRI (fields strengths = 1.5–3T; resolution = 2.2–3.9 × 1.7–2.6 × 2.2–4.0 mm 3 ; Venc = 150–250 cm/s; TE/TR/FA = 2.3–2.8/4.7–5.4msec/7–15°) was performed in 56 controls (age range: 19–78 years) and in two BAV patient groups each consisting of 10 subjects (group 1: 20–29 years, group 2: 52–57 years). Heat maps showing abnormal 3D velocity and WSS were created for the BAV patients by comparison with an age‐matched and with an unmatched control group. The fraction of the aorta exposed to abnormal velocity/WSS was calculated relative to the total aortic volume/surface. Results: Significant inverse relationships between age and healthy velocity/WSS were found (R 2 = 0.32/0.39, P < 0.001). For BAV group 1, abnormally elevated velocity/WSS was overestimated when compared with older controls (51–60 years) than when correctly age‐matched (∼25 ± 14% vs. ∼8 ± 5%). For BAV group 2, abnormally decreased velocity/WSS was overestimated when compared with younger controls (21–30 years) than when correctly age‐matched (∼9 ± 7% vs. 1 ± 1%). Conclusion: Significant correlations exist between age and peak systolic velocity and WSS. Therefore, robust age‐matching is important when creating abnormal 3D aortic velocity and WSS maps for patients with BAV. J. Magn. Reson. Imaging 2016;43:1239–1249.